ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA DITINJAU DARI ADVERSITY QUOTIENT (AQ) - Juhlifa; Hafriani; Lasmi (Prodi Pendidikan Matematika Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
This study aims to describe students’ mathematical creative thinking ability in terms of their Adversity Quotient (AQ) when solving problems related to number patterns, sequences, and arithmetic series. The research employed a qualitative descriptive method with four participants from SMA Negeri 1 Banda Aceh, consisting of two champer and two climber students. Data were collected using questionnaires, tests, and interviews, and analyzed through time triangulation. The results showed that: (1) two students with moderate creative thinking skills had a moderate AQ (champer); one student with moderate creative thinking had a high AQ (climber); and one student with high creative thinking had a high AQ (climber). (2) Efforts to enhance creative thinking included motivation, innovative learning models, non-routine problem exercises, structured assignments, and enrichment activities. The findings indicate a positive relationship between students’ Adversity Quotient (AQ) levels and their mathematical creative thinking abilities.